Design considerations for the mechanical integrity of airgaps in nano-interconnects under chip–package interaction; a numerical investigation. (April 2016) - Zahedmanesh, Houman; Gonzalez, Mario; Ciofi, Ivan; Croes, Kristof; Bömmels, Jürgen; Tőkei, Zsolt
Abstract: Airgaps can undermine the mechanical properties of nano-interconnects and lead to reliability issues such as back end of line (BEOL) fractures. In this context, interconnect delamination under chip–package interaction (CPI) induced loads is a major failure mode which benefits from in-depth investigation. In this computational study, models of airgaps fabricated using the etch-back approach are developed for 90 nm pitch interconnects and potential mechanical failure modes including the fracture energy release rate (ERR) at various material interfaces are investigated. In addition, capacitance benefits of airgap implementation compared to the mainstream low-k technology are calculated using a capacitance simulator. Subsequently, mechanically conscious airgap design strategies are proposed which allow taking advantage of the maximal capacitive benefits of airgaps and limit the CPI related reliability concerns. Highlights: In this study modeling of airgap mechanics and also capacitance was conducted. The thickness of the liner strongly influenced the interfacial energy release rates. Stiff conformal dielectric liners mitigated delamination risks of deeper airgaps. Airgaps reduced capacitance by nearly 30% compared to using ULK 2.4 materials.